Increasing the Payload and Overburden Capacity of the HD785-7 by Adding a Siring Vessel at PT Antareja Mahada Makmur's Mifa Bersaudara Site: May–December 2025 - Bobby Sandy; Muhammad Zulfikar; Muhammad Rizky Mafudz; Desiantoro; Eli Setiawan (Indonesian Journal of Multidisciplinary Science, 2026)
Open-pit mining operations require high hauling productivity to achieve production targets efficiently. However, haul trucks operating under low-density overburden conditions frequently experience suboptimal payload utilisation because the vessel reaches its volumetric capacity before attaining its maximum weight capacity. This condition reduces hauling efficiency, increases operating costs, and constrains overall production performance. Accordingly, this study aimed to evaluate the effectiveness of adding a siring vessel to the HD785-7 haul truck in increasing payload capacity and improving overburden transportation performance at PT Antareja Mahada Makmur, Mifa Bersaudara Site. This research employed a descriptive quantitative approach using a field study and a before-and-after comparative analysis. Operational data including payload, vessel volume, material density, hauling productivity, and production records were collected from May to December 2025 through field observations, direct measurements, company operational databases, and supporting documentation. Root cause analysis was conducted using the Quality Control Circle (QCC) method to identify the primary contributing factors to low payload performance. The results demonstrated that the average payload increased from 86.59 tonnes prior to modification to 97.77 tonnes following modification, representing an improvement of 12.9%. The increased vessel volume enabled the transport of greater quantities of low-density overburden material without compromising equipment stability or structural integrity. In conclusion, the addition of a siring vessel constitutes an effective, practical, and economically beneficial engineering solution for optimising HD785-7 hauling performance under low-density overburden conditions, and may be considered a best practice model for adoption in comparable open-pit mining operations.